Iris metastasis from endometrial carcinoma: A challenging diagnosis and individualized eye-sparing treatment - Alberto Giuseppe Agostara; Annabella Curaba; Giulia Carlo Stella (Elsevier, 2022)
A woman in her 70's with a history of recurrent oral aphthosis and two years earlier of resected stage IA low risk endometrial adenocarcinoma, presented with blurred vision and a painful mass of the right eye that had developed in two months. PET/CT imaging detected a nodule in the right lung. Because of diagnostic uncertainties between inflammatory disease (Behçet syndrome) or cancer, a biopsy of iris and pulmonary lesions were performed and lead to histologically documented metastases from endometrial adenocarcinoma in both sites. After a multidisciplinary team discussion excluding disfiguring local therapies (radiation therapy or surgery), systemic chemotherapy with carboplatin and paclitaxel was performed, leading to radiological complete response that is sustained at 12 months after the end of treatment. This case shows that chemotherapy should be considered as a valid organ-sparing treatment in the management of these uncommon metastatic sites.